Effects of Organic Particle Deposition on Porewater Oxygenation and Oxygen Exchange in Cohesive Sediment - Simone, MN; Hibberd, A; Plew, D; Vopel, K (Inter-Research Science Center, 2025)
This ex situ study utilised oxygen microprofiling and whole-core incubations to investigate potential changes in oxygenation of cohesive sediments resulting from open-ocean fin-fish farming. We examined oxygen conditions in sediments subjected to potential moderate depositional loads (1.1, 2.2, and 3.2 g C m⁻² d⁻¹) of organic farm particles from mariculture expected to settle in dispersive environments. White biofilms formed over particulates that accumulated on the sediment surface after 7 d of at least 2.2 g C m⁻² d⁻¹. Diffusive oxygen uptake (DOU) rates were estimated from sediment microprofiles taken in cores following total oxygen uptake (TOU) determination from whole-core incubations. DOU closely aligned with TOU (DOU:TOU ≈ 1) in cores where biofilms did not develop on the sediment surface (<1.1 g C m⁻² d⁻¹); however, the development of biofilms reduced the DOU:TOU ratio (<1), suggesting the biofilms were responsible for non-diffusive oxygen transport in the TOU. It was speculated that ‘vents’ in the biofilms may have enhanced the solute exchange rates in those cores. The presence of biofilms enhanced benthic TOU, reducing oxygen penetration depths in sediments adjacent to the biofilms by approximately 1 mm compared to unenriched cores. However, these sediments adjacent to biofilms still had an average oxygen penetration of ~2.5 mm, suggesting the patchy accumulation of organic farm particles and development of biofilms on the sediment surface are enhancing the structural heterogeneity of the seafloor and increasing the availability of organic carbon for higher trophic consumers in an otherwise organically deplete system.
Keywords: 0502 Environmental Science and Management; 0602 Ecology; 0704 Fisheries Sciences; 3005 Fisheries sciences; 3103 Ecology; 4105 Pollution and contamination; Sediment oxygenation; Organic deposition; Sediment microprofiling; Biofilm development; Aquaculture